Influence of Security Sector Reforms on Crime Prevention in Juba City, Republic of South Sudan - Mayor, Charles Ciec; Mwangi, Wokabi; Murenga, Hadija (Advances in Social Sciences Research Journal, 2022)
This paper uses data collected for an MA Thesis on the influence of security sector reform on crime prevention in Juba City South Sudan. The study was motivated by the dearth of studies in this academic area and the increased levels of insecurity and crime in Juba and its environs. The study was guided by four objectives; to establish perceptions of the Security Sector Reform Actors on functionality of security institutions roles on crime prevention in Juba City-South Sudan; to assess the influence of Security Sector Reform policies and legal provisions in prevention of crime, to determine the influence of donor technical assistance in prevention of crime and to establish and the nature of obstacles facing SSR and their influence in crime prevention in Juba City-South Sudan.This study was grounded on three theories; Legitimacy Chain, Three Dimensions of Governance, and Control Theories. The study used descriptive survey research design and Simple random sampling method in selecting respondents for the study. Key informants were selected by purposeful sampling. Questionnaires and interview schedules were used as the main data collection tools. This study comprised of 162 main respondents and 20 Key informants respectively. The main method of data collection was the questionnaire. Inferential statistics were used to analyse and present quantitative data. Qualitative data from the interview guide was analyzed by content analysis and presented as verbatim reports and narratives. Amongst other major findings, the study established a relationship between; Functionality of security institutions roles and crime prevention in Juba City-South Sudan as a result of overlapping mandates and duplicity of roles with regard to security forces operations in Juba City-South Sudan. In addition, Donor technical assistance influenced crime prevention (p=0.01).Security Sector Reform policies and legal provisions in prevention of crime, and also donor technical assistance influenced crime prevention in Juba City-South Sudan. The study recommends that the government of South Sudan should ensure that the existing SSR policies and legal provisions are effectively enforced. There is also a need for Government of Sudan in conjunction with international community strengthen the oversight role of parliament and civil society. The study also recommends that there should also be inclusion of communities in the formulation and implementation of SSR policies and legal provisions. The study recommends that the government of South Sudan should seek more donor technical assistance to assist in crime prevention.